The effects of instability core training on balance ability and paddling performance among young male Chinese flatwater sprint kayakers: a randomized controlled trial - Gao, J.; Gong, Z.; Samsudin, S.; Abdullah, B. B.; Dev, R. D. O. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Instability core training (ICT) has been widely used in various sports as a training method to enhance athletes' balance ability and athletic performance. The study aimed to examine the impact of ICT performed on unstable surfaces (BOSU balls, Swiss balls, and Wobble boards) versus traditional core training (TCT) performed on stable surfaces (floor and bench) on balance ability and paddling performance among young male Chinese kayakers.